Better (urban) policies for better lifes. The role of OECD in transnational exchanges of planning ideas in the 1970 - Feriel, Cedric (International Planning History Society Proceedings, 2016)
Transnational History in the field of urban planning largely focused on the first half of the twentieth century (Saunier, Ewen, 2009), although recent works deal with post-war period or after (Planning Perspective, vol. 29, n°2, 2014). The growing role of centralised policies after 1945 explains this, particularly in the case of France or United Kingdom. Nevertheless, it would be abusive to consider that everything came from State administrations. Created in order to advise States, some international organisations reveal, through their works, an another history of transnational exchanges of planning ideas. We offer here to hightlight the work and influence of the OECD on urban planning matters during the 1970s, using the archives of the organisation, located in its headquarter in Paris. At first glance, the institution has nothing to do with planning. In fact, when it was created in 1961, the OECD had no interest on this regard. But in 1969, driven by its new General Secretay, Emile van Lennep, the organisation launched a fundemental environmental turn. Within a new Directorate, a 'Sector Group on the Urban Environment' was created in 1971 whose purpose was to exchange national experiences that could help to improve life in urban areas. Its first assessment was provocatively entitled « exclusion of automobile trafic in downtown areas ». Active throughout the 1970s, the Group worked on many subjects, always using the same method. First, experts had to identify the best local experiences (local level) in order to combine results (transnational level) and finaly make recommandations to States administrations (national level). This way to articulate scales is uncommon for history of exchanges of planning ideas, showing the facilitating role of an international organisation on this regard. This presentation will first contextualise the environmental turn of the organisation that explains its concern about the 'urban environment' and give an overview of the activity of the Sector Group. Then, through the exemple of its first assessment (traffic free areas), it will show the working methods of the group, its contacts at local, national and international levels and the way the organisation dissiminate its conclusions and recommendations. Finally, the presentation will show that, even in such a centralised country as France, the State administration borrowed ideas from OECD's works as a basis for offical acts, suggesting that urban matters had no borders.